Etika Aparatur Sipil Negara Dalam Pelayanan Publik Di Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Yolanda Olifia Sengke; Abdul Rahman Dilapanga; Fitri Herawati Mamonto; taufan alwany (Institut Pemerintahan Dalam Negeri (IPDN), 2023)
Bureaucratic Ethics in Public Service explains where bureaucratic ethics is defined as a system that contains moral principles or influences the habits of civil servants in carrying out a hierarchical government system and a hierarchy of positions as stipulated in Law Number 5 of 2014 concerning State Civil Apparatuses. The focus of this research is the Ethics of State Civil Servants in Public Services at the Regional Education Office of North Sulawesi Province. The method used is a qualitative research method, using Observation, Interview, and Documentation techniques using Equality, Loyalty and Responsibility indicators. Theresults of the study show that for 1. Equality, in general, employees at the Regional Education Office of North Sulawesi Province in providing services in terms of equality have been going well, but not optimal. Because there are still people who think that if you want to take care of files in the office, you need acquaintances who work in the office to get faster processing. 2. Loyalty, regarding Employee Ethics at the Regional Office of Education of North Sulawesi Province in terms of indicators of Loyalty is classified as good. Where, in carrying out their duties as State Civil Apparatus (ASN), employees have carried out their duties properly, helping each other, as well as good communication between fellow employees and the community. 3. Responsibility, in carrying out public service duties at the Regional Education Office of North Sulawesi Province that the ethics of the State Civil Apparatus in providing services is still not conducive. Where there are still employees who make people wait.